A database survey of equine tumours in the United Kingdom. (19th March 2015) - Knowles, E. J.; Tremaine, W. H.; Pearson, G. R.; Mair, T. S.
Summary: Reasons for performing study: Survey data on equine tumours are sparse compared with other species and may have changed over time. Objectives: To describe the most frequently diagnosed equine tumours recorded by a diagnostic pathology laboratory over 29 years, to identify background factors associated with tumour type, and to identify any changes in the tumours diagnosed or the background of cases submitted during the study period. Study design: Observational; cross‐sectional analysis of records of a diagnostic pathology laboratory. Methods: The records of all neoplastic equine histology submissions to the University of Bristol (January 1982–December 2010) were accessed from a database, and a list of diagnoses compiled. The 6 most commonly diagnosed tumour types were analysed using logistic regression to identify background factors associated with tumour type. The overall population of equine tumour submissions and the relative frequency of diagnosis of the most common tumour types were compared between decades. Results: There were 964 cases included. The most frequently diagnosed tumours were: sarcoid (24% cases), squamous cell carcinoma (SCC) (19%), lymphoma (14%), melanoma (6%), gonadal stromal tumour (6%) and mast cell tumour (MCT) (4%). With sarcoid, Thoroughbred/Thoroughbred cross and gelding as reference categories: increasing age was significantly associated with the odds of each of the other tumour types, mares were at reduced risk of SCC, Arab/Arab cross had a higher risk of MCT, Cob/Cob cross had an increased risk of SCC and MCT, and ponies had an increased risk of melanoma. The mean age of submissions increased in each successive decade and the breed composition became broader. Sarcoids and lymphoma formed a smaller proportion of diagnoses in later decades. Conclusions: The types of tumours submitted to this laboratory have changed over the last 3 decades. Current data inform clinicians and researchers and further studies are warranted to follow trends. The Summary is available in Chinese – see Supporting information.